Capacitive Effect and Electromagnetic Coupling on Manganin Gauge Limiting the Bandwidth for Pressure Measurements under Shock Conditions - Antony Coustou; Alexandre Lefrançois; Patrick Pons; Yohan Barbarin (Sensors, 2023)
In this study, we investigated the capacitive effect and the electromagnetic coupling on the measurement chain induced by impact experiments with a gas gun or powder gun. Reduced bandwidth and noise were noticed on experimental signals. Rogowski coil measurements were added on the cables to characterize the electromagnetic coupling. The perturbation currents on the cables were quantified depending on the configuration. The gauge, the transmission line and the conditioning system were modeled. The calculations reproduced the electrical wave arrival time, the transmission line transfer impedance and the conditioning system transfer impedance; and the bandwidth limitation has been displayed. A capacitive effect with the piezoresistive manganin gauge embedded into the sample was identified, depending on the experimental setup.